THU0661 RISK OF PSORIASIS, CROHN'S DISEASE, ULCERATIVE COLITIS AND ANKYLOSING SPONDYLITIS IN PATIENTS WITH UVEITIS: A NATIONWIDE, POPULATION-BASED COHORT STUDY. (June 2019) - Chen, Hsin-Hua; Hsieh, Tsu-Yi; Lin, Ching-Heng; Chen, Yi-Ming; Lai, Kuo-Lung; Chen, Der-Yuan
Abstract : Background: A recent study showed that the risk of ankylosing spondylitis (AS) was increased in patients with uveitis.(1 ) Objectives: The study aimed to test the risk of psoriasis (PsO), Crohn's disease (CD), ulcerative colitis (UC) and AS in uveitis patients. Methods: The data source of this study was the 2003–2012 claims data from the Taiwanese National Health Insurance Research Database. We identified 4, 943 incident patients with uveitis defined as having ≥ 2 ambulatory or ≥1 inpatient visits with a diagnosis of ICD-9-CM 360.12, 364.00–364.02, 364.04–364.05 or 364.3 made by an ophthalmologist from 2006 to 2012 after excluding those having prior PsO (ICD-9-CM 696.1), PsA (ICD-9-CM 696.0), CD (ICD-9-CM 555), UC (ICD-9-CM 556) or AS (ICD-9-CM 720) and randomly selected 49, 430 non-uveitis individuals matching (1:10) uveitis cases for age, sex and the year of the index date from a one million representative population. We estimated the incidence rates of PsO (diagnosed by dermatologists), CD, UC and AS for the uveitis and non-uveitis cohorts, and the incidence rate ratios (IRR) and hazard ratios (HRs) after adjusting for sex, age, Charlson comorbidity index and concomitant medications. Results: No incident case of CD was identified in uveitis patients and non-uveitis individuals. Compared with non-uveitis individuals, patients with uveitis had significantly higher incidence rates of PsO (IRR, 8.82; 95% CI, 6.80–11.43), CD (IRR, 7.23; 95% CI, 1.21–43.27) and AS (IRR, 171.69; 95% CI, 143.15–205.93). However, after adjusting for potential confounders, uveitis patients had a significantly higher risk of developing PsO and AS, but not CD. Conclusion: This nationwide, population-based cohort study revealed that uveitis patients had an increased risk of PsO and AS, but not CD. References: [1] Varkas G, Vastesaeger N, Cypers H, Colman R, Renson T, Praet LV, et al. Association of Inflammatory Bowel Disease and Acute Anterior Uveitis, but Not Psoriasis, With Disease Duration in Patients With Axial Spondyloarthritis: Results From Two Belgian Nationwide Axial Spondyloarthritis Cohorts. Arthritis Rheumatol. 2018;70(10):1588-96. Acknowledgement: We thank the Biostatistics Task Force of Taichung Veterans General Hospital, Taichung, Taiwan, ROC for statistical support. Disclosure of Interests: Hsin-Hua Chen Speakers bureau: Johnson & Johnson, Novartis, Pfizer, Abbvie, Roche, UCB, Bristol-Myers Squibb, Chugai, Tsu-Yi Hsieh: None declared, Ching-Heng Lin: None declared, Yi-Ming Chen Grant/research support from: GSK, Pfizer, BMS, Astra & Zeneca, Consultant for: Pfizer, Novartis, Abbvie, Johnson & Johnson, BMS, Roche, Sanofi, MSD, Guigai, Astellas Inova Diagnostics, UCB Agnitio Science Technology, United Biopharma, Thermo Fisher, Paid instructor for: Pfizer, Novartis, Abbvie, Johnson & Johnson, BMS, Roche, Astra& Zeneca, Sanofi, MSD, Guigai, Astellas UCB Thermo Fisher, Speakers bureau: Pfizer, Novartis, Abbvie, Johnson & Johnson, BMS, Roche, Lilly, GSK, Astra& Zeneca, Sanofi, MSD, Guigai, Astellas UCB Thermo Fisher, Kuo-Lung Lai: None declared, Der-Yuan Chen: None declared